2010
DOI: 10.1016/j.jmmm.2009.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic composites based on hybrid spheres of aluminum oxide and superparamagnetic nanoparticles of iron oxides

Abstract: a b s t r a c tMaterials containing hybrid spheres of aluminum oxide and superparamagnetic nanoparticles of iron oxides were obtained from a chemical precursor prepared by admixing chitosan and iron and aluminum hydroxides. The oxides were first characterized with scanning electron microscopy, X-ray diffraction, and Mössbauer spectroscopy. Scanning electron microscopy micrographs showed the size distribution of the resulting spheres to be highly homogeneous. The occurrence of nano-composites containing aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
3
4
0
1
Order By: Relevance
“…FeO-Fe 2 O 3 and/or maghemite Fe 2 O 3 . By using the Scherrer equation [44] an average size of crystallites was estimated as 9±1 nm that was in excellent agreement with the TEM data.…”
Section: Resultssupporting
confidence: 74%
“…FeO-Fe 2 O 3 and/or maghemite Fe 2 O 3 . By using the Scherrer equation [44] an average size of crystallites was estimated as 9±1 nm that was in excellent agreement with the TEM data.…”
Section: Resultssupporting
confidence: 74%
“…This result was similar to the different supports (10FeAl, 30FeAl, 50FeAl) and the Mössbauer spectra for the 50FeAl sample taken at low temperatures confirm its superparamagnetic state [44], indicating that the incorporation of copper oxide in the composition of the solid did not change the superparamagnetic properties of the material.…”
Section: Denitrification By Cuo/fe 2 O 3 /Al 2 Osupporting
confidence: 85%
“…TEM images indicate the presence of a heterogeneous material which is consistent with the method of preparation for the copper-based sample (wet impregnation), whereas the metal is randomly deposited on the support containing aluminum and iron oxide synthesized by hybrid spheres route, thus, generating particles of different sizes [44]. These results corroborate with the X-ray diffraction profiles, which point to the presence of nanoparticles in the solids, Fig.…”
Section: Denitrification By Cuo/fe 2 O 3 /Al 2 Osupporting
confidence: 84%
See 1 more Smart Citation
“…The diffraction patterns showed that the main reflection peaks at {111}, {220}, {311}, {400}, {422}, {511}, {440}, {533} and {553} can be well indexed with the reference pattern of the Fe 3 O 4 inverse cubic spinel structure (JCPDS card # 08-4611) with spatial group Fd3M. The crystal size calculated by using the Scherrer’s equation [23] showed a magnetite nanoparticle average size of about 11 nm.…”
Section: Resultsmentioning
confidence: 99%